1997
DOI: 10.1007/s11357-997-0001-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-related pathology and biosenescent markers in captive rhesus macaques

Abstract: During the past 15 years, our aging colony of rhesus monkeys, consisting of animals from 20 to 37 years of age, had an annual average population of 88.2 live monkeys and, of this population, an annual average of 13.9 monkeys died spontaneously or were terminated due to severe illness. From 1980 to 1994, a total of 175 autopsies of rhesus macaques, from 20 to 37 years of age, were performed. By cumulative autopsy data, the incidence of age-related pathology in various organs was surveyed. Major geriatric diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 27 publications
3
77
0
5
Order By: Relevance
“…A recent longitudinal study of chronic diseases in aged rhesus macaques has shown an incidence of breast cancer that is comparable to that seen in women in the United States (43). We have identi ed 3 endom etrial polyps in tamoxifen-treated animals, but otherwise neoplasms have not been induced in the relatively short treatment periods used in our studies.…”
Section: Neoplasiamentioning
confidence: 62%
“…A recent longitudinal study of chronic diseases in aged rhesus macaques has shown an incidence of breast cancer that is comparable to that seen in women in the United States (43). We have identi ed 3 endom etrial polyps in tamoxifen-treated animals, but otherwise neoplasms have not been induced in the relatively short treatment periods used in our studies.…”
Section: Neoplasiamentioning
confidence: 62%
“…Menopause involves a gradual decrease in the number and regularity of menstrual cycles, ending with the permanent cessation of menses. A sustained high level of serum luteinizing hormone (LH) concomitant with low levels of estradiol is used as a clinical marker of menopause (Uno 1997). In the absence of sufficient estrogenic stimulation, because of the decrease in circulating levels of estradiol as the result of ovarian aging, the endometrium undergoes progressive involution (Figure 39).…”
Section: Endometrial Agingmentioning
confidence: 99%
“…Moreover, aging Rhesus macaque develops many of the same phenotypes observed in aging humans, including graying and thinning of hair, sarcopenia, and increased incidence of diabetes mellitus, cancer, and other aging-related diseases. 85,86 To date, only 2 major projects have been designed to evaluate the long-term effects of moderate CR on general physiology, health span, and lifespan in nonhuman primates. However, these studies have yielded complex, if not contradictory, results.…”
Section: Caloric Restriction and Nonhuman Primate Studiesmentioning
confidence: 99%